From investment promotion and protection to investment regulation - Crina Baltag (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2020)
While the current framework of international investment law is largely shaped to promote and protect foreign investments, in the past years we have been witnessing a shift to investment regulation. Developing a proper investment regulatory framework should address both substance and procedure while balancing the interests of investors and countries.
Keywords: 330